2007
DOI: 10.1002/eji.200636819
|View full text |Cite
|
Sign up to set email alerts
|

The Th1 immune response against HIV‐1 Gag p24‐derived peptides in mice expressing HLA‐A02.01 and HLA‐DR1

Abstract: Using HLA‐DR1‐transgenic H‐2 class II knockout mice, we identified two new HLA‐DR1‐restricted HIV‐1 Gag p24‐derived epitopes (Gag321–340 and Gag331–350) and confirmed the immunogenicity of seven that have been previously described. The human relevance was confirmed for the two new ones (Gag321–340 and Gag331–350) assaying peripheral blood mononuclear cells from HLA‐DR1+ HIV‐1‐infected long‐term asymptomatic subjects and showing that Gag331–350 could prime CD4+ T cells from two HLA‐DR1+ HIV‐1 seronegative donor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 28 publications
2
5
0
Order By: Relevance
“…34,35 Furthermore, studies show that the lower percentage of CD8 C T lymphocytes does not preclude the use of HLA-A2/DR1 Tg mice for studies of immune responses to pathogens such as HBV and HIV. 34,36 Interesting, it is now well documented by several comparative studies that transgenic HLA class I molecules in chimeric monochain form are superior than traditional transgenic HLA class I molecule mice to induce more efficient T cell responses, even the number of CD8 T cell is lower. 37,38 We also confirmed that HLA-A11/DR1 Tg mice mount efficient and functional humoral and cellular immune responses to a recombinant HBV vaccine and a recombinant HIV-1 protein, and especially mount the specific A11-restricted cellular immune response to a recombinant HIV-1 protein.…”
Section: Discussionmentioning
confidence: 99%
“…34,35 Furthermore, studies show that the lower percentage of CD8 C T lymphocytes does not preclude the use of HLA-A2/DR1 Tg mice for studies of immune responses to pathogens such as HBV and HIV. 34,36 Interesting, it is now well documented by several comparative studies that transgenic HLA class I molecules in chimeric monochain form are superior than traditional transgenic HLA class I molecule mice to induce more efficient T cell responses, even the number of CD8 T cell is lower. 37,38 We also confirmed that HLA-A11/DR1 Tg mice mount efficient and functional humoral and cellular immune responses to a recombinant HBV vaccine and a recombinant HIV-1 protein, and especially mount the specific A11-restricted cellular immune response to a recombinant HIV-1 protein.…”
Section: Discussionmentioning
confidence: 99%
“…Even in this case, expression of transgenic HLA-A2.1 molecule led to an increase in the size of the peripheral CD8+ T cell population, which reached 2–3% of the total splenocytes in HLA-A2/DR1 mice, compared to 0.6–1% in β2m-KO MHC-I deficient mice [12]. Furthermore, this phenomenon had been discussed and several studies on HBV and HIV proved that the low percentage for CD8+ T cell doesn't significantly affect the usage of HLA-A2/DR1 mice in immunological analysis [41], [42].…”
Section: Discussionmentioning
confidence: 99%
“…Cytokine profile analysis of this candidate vaccine showed that the adjuvanted fusion peptide induced an eightfold increase in the IFN-γ/IL-4 ratio leading to a Th1 cytokine pattern compared to the other groups. The shift to a Th1 immune response plays an important role in viral infections such as HIV-1 and this profile facilitates the induction of cellular immunity against viral pathogens (Cristillo et al, 2006;Pajot et al, 2007;Koopman et al, 2008). Humoral immune response and antibody subtypes specific to p24-Nef fusion peptide were also examined.…”
Section: Discussionmentioning
confidence: 99%